2021
DOI: 10.3390/jmse9030244
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of a Planing Hull Using the Smoothed Particle Hydrodynamics Method

Abstract: Computational Fluid Dynamics simulations of planing hulls are generally considered less reliable than simulations of displacement hulls. This is due to the flow complexity around planing hulls, especially in the bow region, where the sprays are formed. The recent and constant increasing of computational capabilities allows simulating planing hull features, with more accurate turbulence models and advanced meshing procedures. However, mesh-based approaches based on the finite volume methods have shown to be lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The finite volume method (FVM) is the most commonly used discretization approach for analysing the hydrodynamic performance of high-speed planning hulls [2]. Studies have shown that the use of unsteady RANSE with the VOF method and FVM, is an effective approach for predicting the hydrodynamic performance of planing vessels [3]. Typically, the spatial discretization is performed using a single mesh, with local refinements in areas of separation and the free surface to accommodate for substantial grid deformations [4,5].…”
Section: Introductionsmentioning
confidence: 99%
“…The finite volume method (FVM) is the most commonly used discretization approach for analysing the hydrodynamic performance of high-speed planning hulls [2]. Studies have shown that the use of unsteady RANSE with the VOF method and FVM, is an effective approach for predicting the hydrodynamic performance of planing vessels [3]. Typically, the spatial discretization is performed using a single mesh, with local refinements in areas of separation and the free surface to accommodate for substantial grid deformations [4,5].…”
Section: Introductionsmentioning
confidence: 99%
“…In this study, a fluid-solid interaction model was established, focusing on the undulation of oil booms under the influence of waves [12]. To achieve singularity of variables, a coupled model of Smoothed Particle Hydrodynamics (SPH) and Chrono was designed to restrict the motion of oil booms in the X and Y axes, thus providing a more accurate simulation of the undulation effect of oil booms [11,13]. In order to realistically reflect turbulence phenomena, an improved Sub-Particle Scale (SPS) turbulence model was adopted, which has higher accuracy and reliability in predicting vortex structures and flow characteristics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Technology development in numerical analysis has been one factor that encourages researchers to conduct numerical analysis-based studies. Numerical analysis of planing hull ships is considered less accurate than displacement hulls [10]. There are methods used in numerical analysis, such as Finite Volume Method (FVM), Finite Element Method (FEM), Finite Difference Method (FDM), and analytic-experiment [11].…”
Section: Introductionmentioning
confidence: 99%